Color Terms Structure in Mountain Environment: โครงสร้างของคำเรียกสีในสิ่งแวดล้อมภูเขา - Chummalee, Penprapa; Chanthao, Rattana (Mekong-Salween Civilization Studies Journal, 2025)
Language is closely linked to society, culture, and the environment. People use words from their language to describe things in their cultural and environmental context. Color terms are closely related to both the environment and the complexity of the culture of the speakers. This study aims to analyze the structure of non-basic color terms in relation to the environment within a mountain context, using the data selection framework for non-basic color terms proposed by Berlin & Kay (1969) and Kay (1975). The color terms were collected using the RAL K7 CLASSIC (2021) color sheets, comprising 93 colors, and interviews with four native speakers aged between 40 and 50 in the research area of the Phu Khiao Mountain Range, Kaset Sombun District, Chaiyaphum Province. The analysis followed the sociocultural linguistics framework of Bucholtz and Hall (2005, 2008) and Hodges (2015). This research employed a qualitative approach and presented the findings in a descriptive analytical format. The results indicated that 372 non-basic color terms were identified, with each term always accompanied by a modifier. These modifiers were closely related to the mountain environment, particularly to local plants. The structure of the non-basic color terms consisted of 26 distinct patterns, which were categorized into 7 structural groups. The most common structure was Group 1, which included the pattern "Color + (modifier + base term)" with 95 terms (25.54%), followed by "Color + (base term + modifier)" with 91 terms (24.46%), and "Color + (primary modifier)" with 74 terms (19.89%). The complexity of these non-basic color term structures reflected a detailed and intricate worldview that connected with the community’s ways of life and culture, as well as the utilization of the mountain environment. These findings demonstrated that geographical factors and the use of environmental resources were closely related to non-basic color terms. The results of this study can be used as a framework for analyzing color terms in other environmental contexts.